Aggressive scripts, violent fantasy and violent behavior: A conceptual clarification and review. (September 2017) - Gilbert, Flora; Daffern, Michael
Abstract: Aggressive scripts are stereotyped aggression-related event sequences typically acquired in early childhood, encoded in memory, rehearsed and elaborated, and then retrieved to guide aggressive behavior. In studies using non clinical and non offender populations, aggressive script rehearsal is commonly reported. Extant research suggests a tendency for aggressive script rehearsal to be activated by perceived personal affronts and constitutes imagined attempts to rebuke wrongdoing by others. Aggressive script rehearsal serves to prepare or rehearse intended acts or stimulate, maintain or regulate emotional or physiological arousal. Despite obvious relevance to violent offender assessment and treatment, research into aggressive script rehearsal is scarce and related terms such as violent fantasy are used interchangeably to describe comparable cognitive processes. Measures designed to assess aggressive scripts and violent fantasy are confounded. Further, few attempts have been made to define and differentiate the terms and there has been little progress in developing treatment procedures addressing these cognitive processes. The current review explores how aggressive scripts and violent fantasy are conceptualised with respect to their key characteristics and proposed acquisition processes and functions, noting commonalities and differences. Their relationship to violent behavior is described. Drawing on knowledge in related areas, including fantasy is likely to assist with the development of insight into the operation and function of aggressive scripts and their relationship to aggressive behavior, with implications for clinical practice. Highlights: Aggressive scripts prepare people to act aggressively; rehearsal also assists regulate emotional or physiological arousal. Aggressive scripts and violent fantasy describe comparable cognitive processes, leading to conceptual confusion. Assessment and intervention approaches to aggressive scripts and violent fantasy are under-developed and require attention.